Retention of Contaminants Elements from Tailings from Lead Mine Washing Plants in Ceramics for Bricks - Suárez Macías, Jorge; Terrones Saeta, Juan María; Corpas Iglesias, Francisco Antonio; Iglesias, Francisco Javier (MDPI, 2020)
Mining activity is essential for the social welfare of the population. However, this activity produces a series of mining waste. These mining wastes, if not properly treated, can produce significant environmental pollution. This study develops the incorporation of tailings from washing plants in ceramic materials for bricks in order to retain the contaminating elements in the ceramic matrix. To this end, firstly, a physical and chemical characterisation of the mining waste is carried out and different groups of samples are conformed with clay and mining waste. These conformed samples with mining waste are evaluated through different physical and mechanical tests typical in the ceramic industry, studying the variation of properties by the incorporation of the waste. In turn, the leachates from the groups of conformed samples are analyzed, confirming the retention of the contaminating elements of the mining waste in the ceramic matrix. The results of these tests showed that ceramics can be made for bricks with up to 90% mining waste, obtaining physical and mechanical properties acceptable regarding the regulations and retaining the contaminating elements in the ceramic matrix, as confirmed by the leachate tests.
Keywords: ceramics; bricks; mining waste; tailings; clay; leachate; sustainability; circular mining; compressive strength